Pretreatment Neutrophil-to-Lymphocyte Ratio as a Prognostic Biomarker in Unresectable or Metastatic Esophageal Cancer Patients With Anti-PD-1 Therapy - Gao, Yiming; Zhang, Zhibo; Li, Yao; Chen, Siyuan; Lu, Jiangyue; Wu, Liangliang; Ma, Zhiqiang; Hu, Yi; Zhang, Guoqing (Frontiers in Oncology, 2022)
Background: Neutrophil-to-lymphocyte ratio (NLR) is an inflammatory index calculated by the absolute neutrophil count dividing the absolute lymphocyte count, and its prognostic role in esophageal cancer (EC) patients with anti-PD-1 therapy remains unclear. Methods: 140 unresectable or metastatic EC patients receiving PD-1 inhibitors treatment were included from Jan 2016 to Mar 2020. Kaplan-Meier method and log-rank test were used for comparing overall survival (OS) and progression-free survival (PFS) between groups. Multivariate cox analysis was performed to assess the prognostic value of NLR. Results: The cutoff value of NLR was set at 5, and the median follow-up time was 20.0 months. Patients with pretreatment NLR < 5 had higher ORR (46.7% vs 12.1%; P < 0.001) and DCR (85.0% vs 69.7%; P = 0.047) than those with NLR ≥ 5. Kaplan-Meier curves showed that pretreatment NLR < 5 was associated with longer PFS (median: 10.0 vs 3.5 months, P < 0.0001) and OS (median: 22.3 vs 4.9 months, P < 0.0001). Multivariate analysis demonstrated that pretreatment NLR ≥ 5 independently and significantly increased the risk of disease progression (hazard ratio [HR] 1.77, 95% confidence interval [CI]: 1.12-2.82; P = 0.015) and death (HR 4.01, 95%CI: 2.28-7.06; P < 0.001). Subgroup analysis showed that pretreatment NLR ≥ 5 was associated with poor efficacy and survival in most subsets. Conclusions: Our findings showed that pretreatment NLR was independently and significantly associated with the efficacy and prognosis of EC patients treated with PD-1 inhibitors. NLR could serve as a convenient and useful prognostic biomarker for EC patients with anti-PD-1 therapy.